"Latent" infection with Toxoplasma gondii: Association with trait aggression and impulsivity in healthy adults. (January 2015) - Cook, Thomas B.; Brenner, Lisa A.; Cloninger, C. Robert; Langenberg, Patricia; Igbide, Ajirioghene; Giegling, Ina; Hartmann, Annette M.; Konte, Bettina; Friedl, Marion; Brundin, Lena; Groer, Maureen W.; Can, Adem; et al.
Abstract: Background: Latent chronic infection with Toxoplasma gondii (T. gondii), a common neurotropic pathogen, has been previously linked with suicidal self-directed violence (SSDV). We sought to determine if latent infection with T. gondii is associated with trait aggression and impulsivity, intermediate phenotypes for suicidal behavior, in psychiatrically healthy adults. Methods: Traits of aggression and impulsivity were analyzed in relationship to IgG antibody seropositivity for T. gondii and two other latent neurotropic infections, herpes simplex virus 1 (HSV1) and cytomegalovirus (CMV). One thousand community-residing adults residing in the Munich metropolitan area with no Axis I or II conditions by SCID for DSM-IV (510 men, 490 women, mean age 53.6 ± 15.8, range 20–74). Plasma samples were tested for IgG antibodies to T. gondii, HSV-1 and CMV by ELISA. Self-reported ratings of trait aggression scores (Questionnaire for Measuring Factors of Aggression [FAF]) and trait impulsivity (Sensation-Seeking Scale-V [SSS-V]) were analyzed using linear multivariate methods. Results: T. gondii IgG seropositivity was significantly associated with higher trait reactive aggression scores among women ( p < .01), but not among men. T. gondii -positivity was also associated with higher impulsive sensation-seeking (SSS-V Disinhibition) among younger men ( p < .01) aged 20–59 years old (median age = 60). All associations with HSV-1 and CMV were not significant. Conclusions: Aggression and impulsivity, personality traits considered as endophenotypes for SSDV, are associated with latent T. gondii infection in a gender and age-specific manner, and could be further investigated as prognostic and treatment targets in T. gondii -positive individuals at risk for SSDV. Highlights: Toxoplasma gondii ( T. gondii ) is associated with suicidal behavior. We examine associations between T. gondii and traits of aggression and impulsivity. T. gondii infection was associated with aggression in women. T. gondii was associated with impulsivity in younger men. These traits may contribute to elevated suicide risk in T. gondii positives.